25th Anniversary, IEEE Conference Record - Abstracts. 1998 IEEE International Conference on Plasma Science (Cat. No.98CH36221) 1998
DOI: 10.1109/plasma.1998.677860
|View full text |Cite
|
Sign up to set email alerts
|

A plasma stealth antenna for the US Navy

Abstract: Energy loss from high-energy electrons that pass through a transmission window causes an increase in window temperature. A technique to cool transmission windows that utilizes water under high pressure flowing in capillary ducts is presented. A model for fluid flow in ducts quantifies fluid pressure, water temperature, convective rate, and vapor pressure as a function of distance into a capillary duct subject to uniform heating.The results quantify a design to prevent vapor formation in a capillary duct and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…Plasma can be used for antenna surfaces to generate low-observability characteristics (Alexef et al 1998). The hollow glass tube filled with low-temperature plasma acts as a plasma-based antenna.…”
Section: Plasma Stealth: History and Futurementioning
confidence: 99%
“…Plasma can be used for antenna surfaces to generate low-observability characteristics (Alexef et al 1998). The hollow glass tube filled with low-temperature plasma acts as a plasma-based antenna.…”
Section: Plasma Stealth: History and Futurementioning
confidence: 99%
“…Plasma antenna originates back from the eighties of 20th century, and various ingenious ways has been devised to achieve such purpose. Plasma can be generated by UV laser irradiation, or by laser initiated pre-ionization followed by high voltage breakdown to form the main conducting channel [4], or by simply using commercial fluorescence tube to serve as reflector [5,6], or by much more expensive electron beam [7][8][9]. There were also exotic methods like explosion generating plasma antenna for fusion research.…”
Section: Introductionmentioning
confidence: 99%
“…Factors of low weight, small size, and the ability to reconfigure during operation, combined with those advantages mentioned above, enable plasma antennas to find wide applications. Kang and Alexeff have demonstrated that it is feasible to construct an antenna with a glass tube filled by low-pressure gas, such as a fluorescent tube [1,2]. Preliminary tests have successfully demonstrated the operation of the plasma antenna with regard to both transmission and reception, and the stealth features have been observed on a navy test range in San Diego.…”
Section: Introductionmentioning
confidence: 99%
“…A large number of antenna configurations with flexible excitation arrangements and DR shapes has been reported with results of DRAs with high radiation efficiency, wide bandwidth, and flexible polarization adjustment [1,2].…”
Section: Introductionmentioning
confidence: 99%